Properties of Concrete with Metakaolin and Eggshell Powder - Mr. Pitti Venkatasuneel, Prof. H. Sudarsana Rao, Dr. Vaishali.G.Ghorpade (International Journal of Advanced Science and Technology, 2020)
In this experimental work, the use of amorphous form of eggshell and metakaolin as partial supplant of cement portion in M30 grade of concrete has been investigated. Egg shell waste from the egg breaking, food processing and shading industries is available in large quantities. Eggshell powder is wealthy in calcium and residences are equal as that of limestone. Metakaolin is pozzolanic material to be used in concrete. Metakaolin is very fine in nature and finer than cement and can be used for making concrete. The research work was carried out with different combinations of metakaolin and egg shell powder as partially replaced by cement. Four distinct proportions as 5%, 10%, 15%, 20% are replaced by the load of cement and the corresponding trade of strength is determined from compression, split tensile and flexural strength tests. Current study presents the conclusion of substitute of cement content with egg shell powder and metakaolin on compression behavior, split tensile property and flexural strengths of concrete grade. Keywords: Concrete, Metakaolin, Eggshell powder, Partial replacement, Compressive strength